Design of Online Exam Information System SMKS Al-Azis Web-Based - Azwar Try Afandi; Deci Irmayani; Budianto Bangun (Jurnal Mantik, 2021)
Along with developments in information technology, the Internet would be helpful. Thanks to the internet, we will be able to conveniently provide services that can be accessed from anywhere in the world at any time. Nowadays, almost everyone has access to knowledge, one of which is the internet. Labuhanbatu Regency's Al-Azis SMKS is a private school. Every year, he finds it challenging to present the questions that his students have submitted. Similarly, at Al-Azis High School, value processing methods are still easy to implement, but it takes a long time. To solve this dilemma, we needed a computerized system to assist schools in progressing and developing. As a result, a web server-based student assessment system and an online review system were developed. Students would be able to see the results of the test immediately after taking it if the instructor processes student exam questions directly. Since this approach provides test score results directly after students have completed the exam. This data system will help teachers allocate grades to their students who have passed the test.